2022
DOI: 10.1108/ijcma-09-2021-0147
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the consequences of workplace incivility: the roles of emotional exhaustion, acceptability and political skill

Abstract: Purpose Workplace incivility is a common deviant behavior happening in organizational contexts, and it can have serious negative consequences such as decreasing employees’ organizational citizenship behavior (OCB) and increasing their turnover intentions. This study aims to test the argument that emotional exhaustion and acceptability of workplace incivility can act as mediators in this relationship between incivility and OCB and turnover intentions. Moreover, the assumption that employees’ political skill can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
31
0
3

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(38 citation statements)
references
References 86 publications
(176 reference statements)
4
31
0
3
Order By: Relevance
“…As environmental factors, deviant workplace behaviors have been extensively explored in organizational behavior research in recent years and have shown to be important antecedents of employee turnover intention. Although the effects of interpersonal deviance (such as workplace bullying and workplace incivility) on the targets' turnover intention have been analyzed (Mahfooz et al, 2017;Malik et al, 2018;Favaro et al, 2021;Moon and Morais, 2022), to our knowledge, no studies have yet examined the effects of negative workplace gossip.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As environmental factors, deviant workplace behaviors have been extensively explored in organizational behavior research in recent years and have shown to be important antecedents of employee turnover intention. Although the effects of interpersonal deviance (such as workplace bullying and workplace incivility) on the targets' turnover intention have been analyzed (Mahfooz et al, 2017;Malik et al, 2018;Favaro et al, 2021;Moon and Morais, 2022), to our knowledge, no studies have yet examined the effects of negative workplace gossip.…”
Section: Introductionmentioning
confidence: 99%
“…One possible way negative workplace gossip affects turnover intention is by influencing ego depletion. Previous studies have mainly explored the influencing mechanisms of deviant workplace behaviors on turnover intention from the perspective of cognition and stress (Mahfooz et al, 2017;Salin and Notelaers, 2017;Malik et al, 2018;Bentley et al, 2021;Moon and Morais, 2022;Schwepker Jr and Dimitriou, 2022). However, the functioning mechanism has not been analyzed from an integrated perspective.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, insecure employment has gained a lot of attention in the workplace; when work stress levels rise, insecurity in the office rises, resulting in increased rates of organizational deviance, burnout, and employee's turnover intensions [11,12]. People have a simple drive to maintain, secure, and create resources which they consider valuable, as per the COR theory [13].…”
Section: Introductionmentioning
confidence: 99%
“…Such influence is exerted to achieve goals under various contextual conditions but in a precise manner (Tang et al, 2020). This dimension is also known as "flexibility" since it allows individuals to adapt and calibrate their behavior according to different scenarios with an intent to elicit the responses they desire from others (Moon & Morais, 2022).…”
Section: Political Skillmentioning
confidence: 99%
“…When they gather and access such critical information needed to perform their job, they gain reputation, power, and promotion. Research proves that political skill not only helps individuals build relationships with leaders but also affects organizational citizenship behavior and promotes the employee's positive emotions towards the organization and its members (Moon & Morais, 2022). Ferris and his colleagues (2007) argue that political skill enhances job satisfaction, and consequently reduces turnover intention.…”
Section: Political Skill and Turnover Intentionmentioning
confidence: 99%